Novel Microstrip Band Pass Filter for C- Band Wireless Applications - S. Sreenath Kashyap, Dr.; MVV Prasad, Kantipudi; Vipul M Dabhi, Dr. (International Journal of Engineering and Technology, 2018)
In this paper, a novel approach for designing the parallel coupled microstrip bandpass filter operating at C-band frequency is numerically analyzed iteratively and simulated. The physical dimensions are being finalized using standard odd- even impedance method. Various electrical parameters such as insertion loss, reflection loss are being analyzed and practical results are being compared and found same as the predicted results. The proposed design is fabricated on FR4 dielectric substrate and the experimental result shows the scientifically acceptable for C-band Applications.Â Â